PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM DESA MAJU - Mohd. Sukran Mupid (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Community Participation in the Program Implementation Desa Maju. This study aims to find out the Program Implementation Inhil Desa Maju Jaya in development planning with the socioeconomic conditions. This research is qualitative. The informants are elements of the district and village communities. Data collection techniques in this study using semi-structured interviews and observation. Analysis of the data in this study using interactive model analysis of Miles and Huberman which includes the step of data reduction, data presentation and verification of data or drawing conclusions. From the research it can be concluded that the process of activity at the level of community participation in the implementation of the Program Desa Maju Jaya Inhil not been implemented optimally and still low. Then the public participation in the implementation of Program Desa Maju Jaya Inhil with socioeconomic relationship with the level of participation is still low.